Análise de painéis enrijecidos em estruturas de casco de FPSOs - Nunes, Mariana Muniz da Silva (2018)
This work presents a buckling analysis in stiffened panels, used in offshore structures type FPSO (floating unit of production, storage and offloading). The region analyzed is located on the starboard side, one of the most demanding locations of the structure. Considering the requirements of the classification societies, a panel, initially intact, had its thickness reduced to the minimum allowed by the rule and from that thickness the integrity of the structure was evaluated. The analysis had continuity with the reduction of the thicknesses to values below the minimum allowed and with the variation of the spacing of the stiffeners. After the analysis were diagnosed the types of failure that occurred in the studied panels. The analysis was performed with the support of the FPSO Eagle ISE phase, developed by the ABS and Finite Element Method, with the support of the TSA phase of the FPSO Eagle program, NASTRAN and FEMAP The results obtained prove that when all the criteria of the prescriptive method are met the structure is indeed reliable. However, the analysis of finite elements proved to be very effective considering the need for a structural reassessment, proving that in some cases it is possible to reduce the thickness without compromising the integrity of the same.